Echocardiography in left atrial thrombosis - Tara Moghaddasfar; Hamed Vahidi; Maryam Faramarzpour; Farnoosh Larti (Clinical Case Reports, 2023)
Abstract Atrial fibrillation is one of the major predisposing factors in developing left atrial thrombosis, leading to morbidity and mortality. Echocardiography plays a paramount role in this condition's detection and subsequent treatment.